Design of a low noise CMOS Op-Amp with high PSRR - The, Yen Ju. (2008)
An integrated circuit design for low supply voltage applications and high quality performance becomes a challenging task in recent years. This report presents a low voltage, low power, low noise and high power supply rejection ratio (PSRR) operational amplifier to drive a resistive load of 10k Ohm in parallel with a capacitive loadof70pF.